Dietary habits and risk of diabetic kidney disease: a two-sample and multivariate Mendelian randomization study - Ziqi Zhang; Jieyu Niu; Wenhao Sun; Yuqing Sun; Ying Tan; Jiangyi Yu (Renal Failure)
Objective We explored the causal relationship between certain dietary habits and the risk of developing diabetic kidney disease (DKD) using two-sample Mendelian randomization and multivariate Mendelian randomization.Research design and methods This study is based on pooled data from a genome-wide association study (GWAS) of 83 dietary habits in a European population. We performed a two-sample Mendelian randomization analysis using GAWS data on diabetic nephropathy in a European population. Validation was then performed against positive results (p < 0.05) in different GAWS data on diabetic nephropathy of European origin. Finally, multivariate Mendelian randomization analyses were performed on dietary habits with positive results (p < 0.05) in both datasets and GWAS data on postprandial glucose in the European population.Results This study showed causal relationships between 18 dietary habits and the risk of developing DKD. After validation, causal relationships were found between the risk of DKD and two dietary habits: abstaining from sugar consumption (OR 2.86; 95%CI 1.35, 6.08; p = 0.006) and consuming whole grain/multigrain bread (OR 0.53; 95%CI 0.32, 0.89; p = 0.016). Correcting for the effect of postprandial glucose, the multivariate MR results showed that never eating sugar increased the risk of developing DKD (OR 0.08; 95%CI 0.018, 0.36; p = 0.001), whereas eating whole grain/multigrain bread did not reduce the risk of developing DKD (OR 1.37; 95%CI 0.55, 3.41; p = 0.50).Conclusions Our MR results suggest a causal relationship between never eating sugar and an increased risk of developing DKD. Therefore, people with diabetes need a reasonable range of sugar intake.